2023
DOI: 10.1101/lm.053781.123
|View full text |Cite
|
Sign up to set email alerts
|

Measuring human context fear conditioning and retention after consolidation

Abstract: Fear conditioning is a laboratory paradigm commonly used to investigate aversive learning and memory. In context fear conditioning, a configuration of elemental cues (conditioned stimulus [CTX]) predicts an aversive event (unconditioned stimulus [US]). To quantify context fear acquisition in humans, previous work has used startle eyeblink responses (SEBRs), skin conductance responses (SCRs), and verbal reports, but different quantification methods have rarely been compared. Moreover, preclinical intervention s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…We employed a configural conditioning task that seeks to maximize configural associations (Stout et al 2018 , 2019 ), thus suggesting hippocampal involvement. In a preceding methodological investigation, we demonstrated successful fear memory recall after 7 days in this paradigm (Xia et al 2023 ).…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…We employed a configural conditioning task that seeks to maximize configural associations (Stout et al 2018 , 2019 ), thus suggesting hippocampal involvement. In a preceding methodological investigation, we demonstrated successful fear memory recall after 7 days in this paradigm (Xia et al 2023 ).…”
Section: Introductionsupporting
confidence: 57%
“…After the trial protocol was registered and recruitment for the present study commenced, we conducted two methodological experiments to investigate the effect size for memory retention in the employed configural fear conditioning protocol (Xia et al 2023 ). These experiments revealed effect sizes between d = 0.58 and d = 0.71 in SEBR, and between d = 0.91 and d = 1.02 in pupil dilation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect sizes for this power analysis were based on a study using cued delay fear conditioning [ 38 ]. After the trial protocol was registered, we derived effect sizes for the CS + /CS- difference in a methodological study [ 36 ] using the same configural fear conditioning paradigm as in the current trial. This study revealed a smaller effect size of d = 0.71 for the CS + /CS- FPS difference.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in the present study, we used a presumably hippocampus-dependent configural fear conditioning paradigm [ 33 35 ] and investigated the effect of minocycline on configural memory retention. We identified the optimal quantification of memory retention in this paradigm in a preceding methodological investigation [ 36 ]. Accordingly, we pre-registered fear-potentiated startle eye-blink responses (FPS) during configural memory recall as primary outcome, and pupil dilation as secondary outcome.…”
Section: Introductionmentioning
confidence: 99%